If it's not what You are looking for type in the equation solver your own equation and let us solve it.
0.5=-2(y+1)
We move all terms to the left:
0.5-(-2(y+1))=0
We calculate terms in parentheses: -(-2(y+1)), so:We get rid of parentheses
-2(y+1)
We multiply parentheses
-2y-2
Back to the equation:
-(-2y-2)
2y+2+0.5=0
We add all the numbers together, and all the variables
2y+2.5=0
We move all terms containing y to the left, all other terms to the right
2y=-2.5
y=-2.5/2
y=-1+0.5/2
| p-7=0.6p+0.4p | | 4x-28=4x+8-3-3x | | 0.5x+0.3x=10 | | 27x-3(x-6)=-6 | | 2(x-3)^2+3=6x+5 | | 2d/8=12 | | 11a+8-a+4=-6 | | -6y-54=-6(y+9) | | (13+2x)(11+2x)=360 | | |z-7|+2=8 | | (13+2x)(11+2x)=217 | | 12x-3x=60 | | 4c/10=9/5 | | 6f+4/2=14 | | X^2-5x-12=24 | | 3b+6=b+3 | | 0.835x=11.42 | | p-7=3/5p+2/5p | | -6Y=x+12 | | 7h+2=12 | | -5(7-10b)=-2(-25b-9) | | (m-2)(m+5)=0 | | 4x-7+4x-7=6x | | (x+2x)-2=1/6*(x=2x) | | 3x-6+3x-6=4 | | x+17+x+17=x+27 | | 23+2x+23+2x=x+22 | | 4/5*x-12=1/5*x | | 2(2x+5)+15=7x+5-3x+20 | | 12x-3=3(4x+3) | | 12x-3=3(4x+) | | 2x-8+2x-8=x+8 |